#### Answer

x = -5
y = - 3

#### Work Step by Step

2x - y = -7
4x - 3y = -11
to the first equation ,minus 2x to both sides
2x - y - 2x = -7 - 2x
-y = -7 - 2x multiply both sides by -1
y = -1 (-7 - 2x ) use the distributive property
y = 7 + 2x
substitude y to the second equation
4x - 3 ( 7 + 2x ) = -11
4x - 21 - 6x = -11
-2x -21 = -11 add 21 to both sides
-2x -21 + 21 = -11 + 21
-2x = 10 divide both sides by -2
$\frac{-2x}{-2}$ = $$\frac{10}{-2}
x = -5 substitude x to y = 7 + 2x
y = 7 + 2 ( - 5)
y = 7 - 10
y = -3